2020
DOI: 10.1016/j.fsi.2020.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increasing dietary level of organic acids and nature-identical compounds on growth, intestinal cytokine gene expression and gut microbiota of rainbow trout (Oncorhynchus mykiss) reared at normal and high temperature

Abstract: Effects of increasing dietary level of organic acids and nature-identical compounds on growth, intestinal cytokine gene expression and gut microbiota of rainbow trout

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 75 publications
3
17
0
1
Order By: Relevance
“…The increased intestinal villi length and a tendency for reduced inflammation found in the present study may indicate increased oxidative capacity and intestinal function [46]. Pelusio, Rossi, Parma, Volpe, Ciulli, Piva, D'Amico, Scicchitano, Candela, Gatta, Bonaldo and Grilli [45] fed a microencapsulated blend of organic acids and essential oils to rainbow trout and found that gene up-regulation involved a limited number of cytokines showing the absence of a substantial inflammation process able to compromise the functional activity of the intestine. Feeding 0.5% essential oils from clove basil improved of phagocytic activity of Nile tilapia (Oreochromis niloticus) [47].…”
Section: Gut Histologymentioning
confidence: 69%
See 2 more Smart Citations
“…The increased intestinal villi length and a tendency for reduced inflammation found in the present study may indicate increased oxidative capacity and intestinal function [46]. Pelusio, Rossi, Parma, Volpe, Ciulli, Piva, D'Amico, Scicchitano, Candela, Gatta, Bonaldo and Grilli [45] fed a microencapsulated blend of organic acids and essential oils to rainbow trout and found that gene up-regulation involved a limited number of cytokines showing the absence of a substantial inflammation process able to compromise the functional activity of the intestine. Feeding 0.5% essential oils from clove basil improved of phagocytic activity of Nile tilapia (Oreochromis niloticus) [47].…”
Section: Gut Histologymentioning
confidence: 69%
“…Using electrophoresis methods, studies on rainbow trout and red drum have not found significant effects of essential oils on the gut microbiome [30,31]. Similarly, Pelusio, Rossi, Parma, Volpe, Ciulli, Piva, D'Amico, Scicchitano, Candela, Gatta, Bonaldo and Grilli [45] found no significant effect of organic acids and essential oils on the alpha-diversity (Shannon and Chao1) of gut microbiota in rainbow trout using next-generation sequencing. There was a trend towards reduction of Streptococcus in fish feed higher inclusion diets, whereas the present study found higher abundance of Streptococcus (Table 4).…”
Section: Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, while fish fed with L16 diet showed significant gut microbiome changes only at the autumn shift, parallel with a reduction in ecosystem diversity, for the L21 diet, both summer and autumn temperature shifts resulted in significant variations in the ecosystem. Temperature is known to modulate microbial diversity in animals especially in poikilothermic fish species (Sepulveda and Moeller, 2020); however, data explaining the interaction between diet and temperature changes in fish are scarce (Soriano et al, 2018;Busti et al, 2020b;Pelusio et al, 2020). Interestingly, among the few studies, which underlined the combined effect of temperature and dietary lipid level, Soriano et al (2018), in yellowtail kingfish, detected a reduced bacterial abundance and richness associated to a suboptimal low temperature and low dietary lipid level, suggesting that gut microbiome composition could maintain high relative abundance after the decrease in temperature only in the presence of appropriate nutritional conditions, pointing out the importance of optimal lipid level at low temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Ante esta situación, estudios en los últimos años realizados en especies terrestres han encontrado compuestos, que pueden ser nutrientes o no, que confieren beneficios en el rendimiento productivo y la salud intestinal de los organismos que lo consumen (Øverland et al, 2019). Los beneficios potenciales y que pueden ser posibles alternativas a los antibióticos han generado un gran interés en el uso de estos compuestos funcionales en la acuicultura para mejorar la productividad y salud de los animales de cultivo (Pelusio et al, 2020), especialmente, cuando las dietas incluyen ingredientes de origen vegetal. Dentro de los compuestos funcionales podemos encontrar aminoácidos ácidos grasos -esenciales o no-, ácidos grasos de cadena corta, carotenoides, pigmentos, péptidos bioactivos, ácidos orgánicos, pre y probióticos, compuestos activos de plantas, nucleótidos, entre otros.…”
Section: Introductionunclassified